Chromophoric and Dendritic Phosphoramidites Enable Construction of Functional Dendrimers with Exceptional Brightness and Water Solubility. Issue 38 (8th August 2014) - Shaller, Andrew D.; Wan, Wei; Zhao, Baoming; Li, Alexander D. Q.
Abstract The fluorescence brightness of a molecular probe determines whether it can be effectively measured and its water solubility dictates if it can be applied in real‐world biological systems. However, molecules brighter than the most efficient fluorescent dyes or particles brighter than quantum dots are hard to come by, especially when they must also be soluble in water. In this report, chromophoric phosphoramidites are used in a solid‐state synthesis to construct functional dendrimers. When highly twisted chromophores are chosen and the proper spacers and dendrons are introduced, the resultant dendrimers emit exceptionally bright fluorescence. Chromophores, spacers, and dendrons are stitched together by efficient phosphoramidite reagents, which afford high‐yield water‐soluble phosphodiester linkages after deprotection. The resulting water‐soluble dendrimers are exceptionally bright.